Radioactivity levels and concentrations of heavy elements in black sand - Ibrahim, Noorddin (Malaysian Journal of Science, 1999)
The radioactivity levels and concentrations of heavy elements in Langkawi black sand have been studied through gamma ray spectroscopy. Direct gamma counting was used for measuring the activity of the natural radionuclides uranium, thorium and potassium, and neutron activation analysis for detecting the presence of other heavy elements. Our results show the activity of uranium is 44.5 pCi g-1, which is four times higher than that of thorium (11.6 pCi g-1) and eight times that of potassium (5.5 pCi g-1). 7. Ytterbium, thorium, europium, cesium, antimony, scandium, gallium, iron, chromium, cobalt, cerium, arsenic lanthanum, samarium and hafnium were detected; their concentrations range from 4.9 to